The Relationship between students’ engagement, grit, and teacher care in Chinese context - Xin Wang; Jianguo Xiao (PLoS ONE, 2025)
The significant growth in the field of English as a Foreign Language (EFL) education, along with the introduction of Positive Psychology (PP), has led to an increased emphasis on student engagement within the academic realm. Additionally, the focus on grit in language education highlights its importance in students’ success throughout their educational journey. Besides, learners’ engagement in academic domains is a noteworthy supporting the achievement of students in higher education. Also, the investigation of favorable communication actions has been examined as an important indicator of EFL learners’ engagement and grit. However, the significance of teacher caring in predicting EFL learners’ grit and engagement has been underresearched among Chinese EFL learners and this study makes an effort to consider it. To fill this gap, 401 EFL learners from 11 regions of China were requested to respond to three scales, namely engagement, grit, and teacher care. The data were collected and through Structural Equation Modeling (SEM), it was revealed that about 59 percent of changes in the EFL learners’ grit can be predicted by their teacher care, and about 67 percent of changes in the EFL students’ engagement can be predicted by their teacher care. Finally, the suggestions for the results are also presented.